ESTIMATES OF WAVE ENERGY SPECTRA IN MALAYSIAN WATERS - NORDIN, AZMI HADZALIE (2016)
Offshore engineering design and operation considerations are being made with reference to standards and codes such as PETRONAS Technical Standard (PTS) where a current wave spectral model being adopted in PTS is the JONSWAP and Pierson-Moskowitz (P-M) spectrum. In the design and operation of offshore oil and gas facilities, actual metocean conditions are crucial in order to operate safely and economically for the strength, durability and serviceability state of the facilities over the designed life span of the structures. The JONSWAP and P-M wave energy spectra, were derived for the North Sea and North Atlantic Ocean respectively compared to the one derived for South China Sea (SCS). This gap in the past resulted in the use of a much conservative value in engineering design, where a significant wave height (Hs) to peak period squared (Tp2) relationship is found to be 0.04 in P-M and 0.04938 in JONSWAP wave energy spectra respectively.